The Role of Stakeholders on Successful of Tourism Event Rendang Journey Culinary Event in Indonesia - Maranisya, Ulfi (Jurnal Penelitian Pariwisata, 2021)
This event was carried out before the Covid 19 pandemic. This research was conducted to provide education and applications that an event concept can be used as the knowledge that can educate the public. In addition, the purpose of this research has not been found with the concept of a similar event with the same target and results as the successful event of the Rendang Journey. Today, MICE (Meeting, Incentive, Convention, Exhibition) is an industry that can drive a generator of economic growth. The growth of the meetings and conventions industry has been stimulated by the growth of the knowledge economy. Planning an event can’t be done in a short amount of time. Preparation of an event with the concept of- mature and well-directed will produce a successful event. Rendang Journey is a Culinary Tourism for culture, with youth generation as the target, and three serial activities, Seminar & Talkshow, Creations of Rendang Cooking Competition, and Culinary Tours to West Sumatera. The research methodology uses a mixed qualitative approach and quantitative (mixed methods) case studies to see the role and contribution of culinary tourism events to tourism policy. Data were collected using questionnaires and interviews as supporting data and confirmation to respondents. Keywords: Culinary Tourism, Rendang, Tourism Stakeholders